Implementación de un algoritmo multiobjetivo para la compensación óptima de potencia reactiva en el sistema eléctrico Ecuatoriano. - Vega Herrera, Denilson Joel (2023)
This research project is centered around optimizing the placement of reactive power compensation in electrical systems to enhance efficiency and power supply stability. To achieve this, a multi-objective algorithm has been developed to minimize active power losses and costs linked to the positioning of reactive compensation devices. This approach considers various criteria and technical constraints to achieve these devices optimal placement and sizing. The algorithm's validation uses the IEEE 30 Bus system, where different demand scenarios are generated to assess its performance. Once the algorithm's validation is completed, it is applied to demand scenarios for the Ecuadorian National Interconnected System, utilizing the DIgSILENT PowerFactory software and referring to previous research. The system has been simplified in this case, considering essential data concerning buses, generators, transformers, and transmission lines.